Fructose Malabsorption in Systemic Sclerosis. Issue 39 (September 2015) - Marie, Isabelle; Leroi, Anne-Marie; Gourcerol, Guillaume; Levesque, Hervé; Ménard, Jean-François; Ducrotte, Philippe; Kantarceken., Bulent
<x xml:space="preserve">Abstract</x> Abstract The deleterious effect of fructose, which is increasingly incorporated in many beverages, dairy products, and processed foods, has been described; fructose malabsorption has thus been reported in up to 2.4% of healthy subjects, leading to digestive clinical symptoms (eg, pain, distension, diarrhea). Because digestive involvement is frequent in patients with systemic sclerosis (SSc), we hypothesized that fructose malabsorption could be responsible for intestinal manifestations in these patients. The aims of this prospective study were to: determine the prevalence of fructose malabsorption, in SSc; predict which SSc patients are at risk of developing fructose malabsorption; and assess the outcome of digestive symptoms in SSc patients after initiation of standardized low-fructose diet. Eighty consecutive patients with SSc underwent fructose breath test. All SSc patients also completed a questionnaire on digestive symptoms, and a global symptom score (GSS) was calculated. The prevalence of fructose malabsorption was as high as 40% in SSc patients. We also observed a marked correlation between the presence of fructose malabsorption and: higher values of GSS score of digestive symptoms (P = 0.000004); and absence of delayed gastric emptying (P = 0.007). Furthermore, in SSc patients with fructose malabsorption, the median value of GSS score of digestive symptoms was lower after initiation of standardized low-fructose diet (4 before vs. 1 after; P = 0.0009). Our study underscores that fructose malabsorption often occurs in SSc patients. Our findings are thus relevant for clinical practice, highlighting that fructose breath test is a helpful, noninvasive method by: demonstrating fructose intolerance in patients with SSc; and identifying the group of SSc patients with fructose intolerance who may benefit from low-fructose diet. Interestingly, because the present series also shows that low-fructose diet resulted in a marked decrease of gastrointestinal clinical manifestations in SSc patients with fructose malabsorption, our findings underscore that fructose malabsorption may play a significant role in the onset of gastrointestinal symptoms in these patients. Finally, we suggest that fructose malabsorption may be due to reduced fructose absorption by enterocytes, impaired enteric microbiome, and decreased intestinal permeability.